Genetic Analysis of Population Structure Using Peroxidase Gene and Phenylalanine Ammonia‐Lyase Gene‐Based DNA Markers: A Case Study in Jute (Corchorus spp.). Issue 4 (1st July 2014) - Satya, Pratik; Banerjee, Ruby; Biswas, Chinmay; Karan, Maya; Ghosh, Swagata; Ali, Nasim
ABSTRACT: Information on genetic structure of population and crop genetic diversity provides crucial input for genetic improvement of crop species. Plant peroxidase gene (POG) and phenylalanine ammonia‐lyase gene (PALG) sequences are multigene families that can be used to design DNA marker systems for genetic diversity and population structure analysis. In the present study, genetic diversity and population structure of 110 Corchorus genotypes were investigated with 17 POG and six PALG markers and compared with results based on 15 simple sequence repeat (SSR) markers. A protocol for using PALG sequences as DNA markers was established, and an earlier protocol for POG marker system was improved. A total of 269 POG and PALG loci were identified revealing 89.2% and 98.5% polymorphism for POG and PALG markers, respectively. The SSR markers amplified 61 alleles in the population. The PALG markers generated comparatively more number of observed and effective alleles, with higher Shannon's information index and expected heterozygosity. Pairwise comparison of population using Nei's genetic distance and genetic identity revealed close association between geographically isolated populations of C. olitorius . Wild Corchorus species exhibited more genetic association with C. olitorius than C. capsularis . Analysis of molecular variance identified 67, 88, and 56% within population variations for POG, PALG, and SSR, respectively. Bayesian structure and hierarchical clustering analyses based on POG polymorphism identified five distinct groups and allelic variations between geographically isolated Indian and African C. olitorius populations with low genetic admixture. PALG‐based population structure analysis revealed three groups with high genetic admixture among populations, while SSR‐based structure identified three genetic groups with low admixture. A combination of all the marker systems improved population structure‐based classification, fitting well to phylogenetic classification. The results establish POG and PALG markers as efficient functional DNA marker systems and provide valuable information for genetic enhancement of cultivated Corchorus species.